Imunopatogenia da interação entre acrófagos e/ou células de Langerhans e Lacazia loboi - YAMANO, Suellen Sirleide Pereira (Universidade Federal do Pará, 2014)
Lobomycosis is a chronic, granulomatous, fungal infection of the skin and subcutaneous caused by the fungus Lacazia loboi. This mycosis occurs predominantly in Amazon region and affect all populations groups. Histologically, there is a chronic inflammatory reaction characterized by the intense fibroplastia and histiocytosis, abundant number of macrophages, multinucleated giant cells and presence of large numbers of yeast. Macrophages are phagocytic cells that participate in the recognition and response to pathogens through phagocytosis, antigen presentation to T lymphocytes and cytokine production. Langerhans cells (LC) are a group of dendritic cells (DC) derived from bone marrow, which are located mainly in the suprabasal layer of the epidermis. Studies on hostfungal interaction in Jorge Lobo's disease are scarce. Therefore, this study constitutes an important step towards a better understanding of L. loboi biology and pathogenesis, enabling in vitro culture of this organism endemic in Amazon region and study of their antigenic properties, as well as new therapeutic approaches. The objective of this study was to analyze the in vitro interaction between non-activated peritoneal macrophages and/or Langerhans cells isolated from BALB/c mice and L. loboi, calculating infection, phagocytosis and cellular fusion rates; also measuring the production of TNF, IL-4, IL-6, IL-10 and IL-12. Results showed that L. loboi is phagocytosed by macrophages but not by LC. Phagocytosis and infection rates in the interaction between macrophages and L. loboi was similar to interaction between macrophages, Langerhans cells and L. loboi at all times analyzed. The mean number of yeast cell per macrophage was almost equal among interactions and over time, with mean variation from 1.2 to 1.6 yeast/macrophages. No giant cells formation in coculture studied. No significant difference occurred in IL-4, Il-2 and IL-10 production between interactions studied. TNF levels decrease in interaction between macrophages and L. loboi while adding LC induces increased production of TNF-α, especially after 48 hours. LC negatively modulate IL-6 production by macrophage and L. loboi also inhibits this production by macrophages alone or cocultured with LC. L. loboi stimulated significantly IL-12 production by macrophages co-cultured with LC, but not for LC alone or macrophages.